Assessment of midbrain atrophy in patients with progressive supranuclear palsy with routine magnetic resonance imaging - Cosottini, M.; Ceravolo, R.; Faggioni, L.; Lazzarotti, G.; Michelassi, M. C.; Bonuccelli, U.; Murri, L.; Bartolozzi, C. (Acta neurologica Scandinavica, 2007)
Objectives –  To assess midbrain atrophy through morphometric (linear, surface and volumetric) measurements in patients with clinically diagnosed progressive supranuclear palsy (PSP) and to establish the most accurate measure to be implemented in routine magnetic resonance (MR) protocol in distinguishing PSP from healthy subjects and MSA‐p (multiple system atrophy, parkinsonian form) patients. Materials and methods –  We studied 15 patients with the diagnosis of probable PSP, seven patients with the diagnosis of probable MSA‐p and 14 age‐matched healthy volunteers. MR protocol includes a sagittal SE T1‐weighted sequence for cross‐sectional area and linear brainstem measurements and a 3D‐FSPGR sequence for brainstem volume measurements. Results –  A highly significant difference in the antero‐posterior midbrain diameter, area and volume in PSP compared with control subjects was found. Only a measurement of the midbrain area and pons area enabled one to distinguish between PSP and MSA‐p. Receiver operating characteristic analysis revealed that the midbrain area has the highest diagnostic accuracy in distinguishing between PSP and other conditions, with a sensitivity of 100% and specificity of 90.5%. The addition of the midbrain area/pons area ratio (Ams/Apn ratio) measurement improves the specificity in distinguishing between PSP and MSA. Conclusions –  Morphological indexes indicate midbrain atrophy in PSP patients The combination of the Ams and Ams/Apn ratio measurements allows to discriminate between PSP and other conditions.